Membumikan Yang Di Menara Gading: Dari Dikotomi Ke Integrasi Menuju Hilirisasi Ilmu Pengetahuan Perguruan Tinggi Islam Di Indonesia - Moch Iqbal (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
The purpose of this paper is to examine scientific discourse in universities as an effort to improve the quality and competitiveness of universities under the auspices of the Ministry of Religion. Using the literature review method, by tracing written sources in the form of books and scientific journals that are available offline and online. The results of the study show that first, state Islamic religious universities have been struggling with narrow scientific studies for too long, so that they seem to keep their distance from general science and technology. Second, the scientific dichotomy between religion and science is a colonial product. Third, a new awareness emerged of Islamic scholars after the New Order to integrate religious and scientific knowledge and was supported by the government by encouraging state Islamic universities to become universities. Fourth, until entering the 20th year after the transfer of status to a university (UIN Syarif Jakarta, 2002), it still has not shown encouraging results for scientific products, especially science and technology. Fifth, there needs to be more grounding/downstreaming of Islamic higher education science in the midst of society.